2022
DOI: 10.37201/req/013.2022
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy of switching to bictegravir/ emtricitabine/tenofovir alafenamide in pretreated patients with triple therapy containing rilpivirine

Abstract: Objective. To analyze the efficacy and tolerability of the strategy to change from rilpivirine (RPV) based regimens to bictegravir / emtricitabine / tenofovir alafenamide (B/F/TAF). Methods. Single-center, observational and retrospective study. Patients who made the change to B/F/TAF before February 2020 were selected, analyzing the results after 24 and 48 weeks. The percentage that remained with an undetectable viral load was determined, as well as the changes in CD4 + lymphocytes, metabolic parameters and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Our results are similar to those observed in previous real-life studies in Spain. 22,27 For instance, in the study of Ambrosioni and colleagues, effectiveness in TN and TE patients was 63% and 78%, respectively, and these values were similar in our cohort (62% and 75%).…”
Section: Discussionsupporting
confidence: 78%
“…Our results are similar to those observed in previous real-life studies in Spain. 22,27 For instance, in the study of Ambrosioni and colleagues, effectiveness in TN and TE patients was 63% and 78%, respectively, and these values were similar in our cohort (62% and 75%).…”
Section: Discussionsupporting
confidence: 78%
“…In a study conducted in patients over 50 years of age with treatment experience, virological success was observed to continue [22]. A study in Spain showed that among treatment-experienced PLWHs who switched to BIC/FTC/TAF, undetectable HIV viral loads persisted at 48 weeks [23]. In our cohort, switching to BIC/FTC/TAF was associated with the maintenance of virological suppression at week 48.…”
Section: Discussionmentioning
confidence: 52%